Oliver Cosgrove interviewed by Christine Choo for the Forgotten Australians and Former Child Migrants oral history project - Cosgrove, Oliver, 1949-; Choo, Christine (2012)
Oliver Cosgrove was born (1949), in a lying-in home for unmarried women in London. He talks about: Catholic Child Migrant Scheme; Nazareth House; St Vincent's Foundling Home; St Joseph's Orphanage; Sisters of Mercy; Christian Brothers; living conditions and treatment of the children in the institutions, Castledare, Clontarf; quality of the schooling; Aboriginal worker Rosie Finnucane; British child migrants; treatment during weekend outings to families; family in Ireland; Catholic Child Welfare Council; The Scheme and Reaping the Whirlwind by Barry Coldry; New South Wales Supreme Court; employment; National Service (1970) and Vietnam; teaching career; culture of mining towns; isolation, mental health and institutionalisation; post traumatic stress; Sexual Assault Referral Centre (SARC); retirement (2009); Department of Veterans' Affairs (DVA); CBERS (Christian Brothers Ex Residents' Services); Department for Family and Children's Services; Class Actions in New York, (The Alien Tort Statute) and in Australia with Slater & Gordon; Apology to Forgotten Australians; Reconciliation Commission; Redress Scheme; identity and acceptance; reflections on his life, family and survival.
Recorded on 2, 3 and 9 February 2012 in Bicton, W.A.
Mode of access: Online.
Timed summary (10 p.)
Keywords: Cosgrove, Oliver, -- 1949- -- Interviews; Castledare Junior Orphanage (W.A.) -- History; Clontarf Boys' Town -- History; Children -- Institutional care -- Western Australia -- History -- 20th century; Immigrant children -- Western Australia; Teachers